Teaching Quality Mediation: Contributions to the Principal’s Strategy with the Competency of Students - Adam, Firman; Komariah, Aan; Kurniady, Dedy Achmad (International Journal of Psychosocial Rehabilitation, 2020)
The study aims to describe the influence of the principal’s strategy on student competence and indirect influence through teaching quality mediation. Data is obtained from 45 vocational schools in Bandung City and analyzed by the path of analysis. The results of the research obtained the scale score of P-values strategy of the school principal towards the teaching quality of 0.210 while the indirect influence of the principal’s strategy on the competency of students through the teaching quality of 0.003. Based on the P-value, it can be concluded that: 1) The principal’s strategy has no significant effect on the student’s competence; 2) The quality of teaching is capable of dissemination of the relationship between managerial strategies and students ’ competence. As a recommendation, in formulating the principal strategy should prioritize on giving teachers the opportunity to focus more on students by reducing the administrative burden of the teaching.